Manajemen Periklanan Star Radio dalam Menjaga Loyalitas Pengiklan - Cindy Salsabilla; H. H Daniel Tamburian (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2021)
The development of the digital era that brings a new lifestyle, it certainly has an impact on other communication media. One of the communication media that feels this impact is radio. Radio listeners in the community are increasingly declining. However, beyond that, there are still many radio stations that are still able to maintain their existence, namely Star Radio Tangerang. Although it has experienced a phase of ups and downs, Star Radio Tangerang has successfully maintained its existence by collaborating with old media and new media. Star Radio Tangerang advertises interesting programs in accordance with the wishes of advertisers and provides these advertisements to their listeners and ends up as an additional attraction to grow the loyalty of advertisers and listeners. The success of Star Radio Tangerang cannot be separated from the role of advertising management. By using a qualitative descriptive method, the research would like to describe how the efforts of Star Radio Tangerang in maintaining Advertiser Loyalty. The data analyzed are the results of interviews with four Star Radio sources, direct observations of Star Radio broadcasting, as well as a review of documents relating to Star Radio advertising management. The results of this study indicate that Star Radio management has implemented the stages and management strategies in the process of making advertisements optimally. In addition, Star Radio also strives to optimize communication with advertising and to use after sales services in an effort to form advertiser loyalty.Dengan berkembangnya era digital yang menghadirkan gaya hidup baru, tentu memberikan dampak pada media komunikasi lainnya. Salah satu media komunikasi yang merasakan dampak ini adalah radio. Pendengar radio di masyarakat kian hari kian menurun. Namun, di luar itu semua masih banyak stasiun radio yang tetap mampu mempertahankan eksistensinya, yaitu Star Radio Tangerang. Meskipun pernah mengalami fase naik-turun, Star Radio Tangerang sukses mempertahankan eksistensinya dengan melakukan kerjasama antara media lama dengan media baru. Star Radio Tanggerang mengiklankan program-program yang menarik sesuai dengan keinginan pengiklan dan memberikan iklan tersebut kepada para pendengarnya dan berujung sebagai daya tarik tambahan untuk menumbuhkan loyalitas pengiklan dan pendengar. Kesuksesan Star Radio Tangerang ini tidak lepas dari peran serta manajemen periklanan. Dengan menggunakan metode deskriptif kualitatif, penelitian ingin menguraikan bagaimana upaya manajemen Periklanan Star Radio di Tangerang dalam menjaga Loyalitas Pengiklan. Data yang dianalisis merupakan hasil wawancara dengan empat narasumber Star Radio, pengamatan langsung penyiaran Star Radio, serta telaah dokumen yang berkaitan dengan manajemen periklanan Star Radio. Adapun hasil penelitian ini menunjukan bahwa manajemen Star Radio telah menerapkan tahapan-tahapan dan strategi manajemen dalam proses pembuatan iklan secara optimal. Selain itu, Star Radio juga mengupayakan optimalisasi komunikasi dengan periklanan serta menggunakan layanan after sales dalam usahanya membentuk loyalitas pengiklan.